2017
DOI: 10.1016/j.concog.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Prestimulus alpha-band power biases visual discrimination confidence, but not accuracy

Abstract: The magnitude of power in the alpha-band (8–13 Hz) of the electroencephalogram (EEG) prior to the onset of a near threshold visual stimulus predicts performance. Together with other findings, this has been interpreted as evidence that alpha-band dynamics reflect cortical excitability. We reasoned, however, that non-specific changes in excitability would be expected to influence signal and noise in the same way, leaving actual discriminability unchanged. Indeed, using a two-choice orientation discrimination tas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
175
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(213 citation statements)
references
References 54 publications
31
175
7
Order By: Relevance
“…Indeed, due to lack of a time dimension to track evidence accumulation, SDT cannot distinguish between these two possibilities 3,4 . Thus far, trial-to-trial variations in the criterion have been shown to correspond to spontaneous fluctuations in neural excitability, as measured in prestimulus oscillatory cortical activity in the 8-12 Hz (alpha) band [4][5][6] . Alpha oscillations, in turn, have been proposed to be involved in the gating of task-relevant sensory information 7 , in line with adaptive regulation of evidence accumulation.…”
mentioning
confidence: 99%
“…Indeed, due to lack of a time dimension to track evidence accumulation, SDT cannot distinguish between these two possibilities 3,4 . Thus far, trial-to-trial variations in the criterion have been shown to correspond to spontaneous fluctuations in neural excitability, as measured in prestimulus oscillatory cortical activity in the 8-12 Hz (alpha) band [4][5][6] . Alpha oscillations, in turn, have been proposed to be involved in the gating of task-relevant sensory information 7 , in line with adaptive regulation of evidence accumulation.…”
mentioning
confidence: 99%
“…Although dominant models suggest that confidence reflects an optimal readout of the probability that a decision is correct (Ratcliff and Rouder, 1998;Ratcliff and McKoon, 2008;Pleskac and Busemeyer, 2010;Tsetsos et al, 2012;Fetsch et al, 2014;Kiani et al, 2014;Pouget et al, 2016;Sanders et al, 2016;Zylberberg et al, 2016), it appears challenging for such models to account for counterintuitive behaviors in which confidence and accuracy do not covary (Rahnev et al, 2011(Rahnev et al, , 2012a(Rahnev et al, , 2012bKoizumi et al, 2015;Maniscalco et al, 2016;Samaha et al, 2016). An alternative hypothesis suggesting that confidence reflects a heuristic reliance on decision-congruent evidence (Zylberberg et al, 2012;Koizumi et al, 2015;Maniscalco et al, 2016;Samaha et al, 2016Samaha et al, , 2017 captures many of these behaviors, and is supported by human intracranial electrophysiology (Peters et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…In light of this discussion, and of the empirically observed tuned normalization in cortical areas, a biologically plausible model of sensory evidence accumulation ought to implement more than one level of lateral inhibition and consider how such tuned normalization may affect a neuron's role in the circuitry. Further, such stratification of tuned normalization could provide a neural mechanism to explain findings that confidence judgments rely on the magnitude of decisioncongruent evidence (Zylberberg et al, 2012;Aitchison et al, 2015;Koizumi et al, 2015;Maniscalco et al, 2016;Peters et al, 2017b;Samaha et al, 2017). Specifically, the output of less normalized 'detection' neurons could be used to index decision-congruent evidence and therefore be used for confidence rating.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively undisputed that alpha power lateralization tracks the locus and timing of spatial attention (Bae & Luck, 2018;Foster et al, 2017;Samaha, Iemi, & Postle, 2017). In addition, a growing body of evidence supports the notion that the alpha rhythm as a correlate of spatial attention, so far predominantly investigated in the visual attention literature, analogously operates in different modalities (Haegens et al, 2011;Klatt et al, 2018aKlatt et al, , 2018bThorpe, D'Zmura, & Srinivasan, 2012;Wöstmann et al, 2016Wöstmann et al, , 2018.…”
Section: Is Post-stimulus Alpha Power Lateralization Functionally Relmentioning
confidence: 94%